Uma quitosanase recombinante de Chromobacterium violaceum ATCC 12472 produz quitooligossacarídeos com atividade antifúngica - Azevedo, Mayara Itala Gerônimo de (2020)
Chitosan is a polymer of β-D-glucosamine and N-acetyl-β-D-glucosamine subunits, found in the cell wall of fungi. Chitosanases (EC 3.2.1.132) are enzymes capable of degrading chitosan into low molecular weight oligomers. It has been shown that chitosan oligomers exhibit various biological activities, including potent antimicrobial, antitumor, and anti-cholesterol activities, among others. Thus, it is extremely important to produce these molecules in a reproducible, environmentally friendly way, at high temperatures and at low cost, characteristics brought about only by the enzymatic hydrolysis of chitosan. Therefore, this work aimed to produce a recombinant chitosanase from C. violaceum and to evaluate a biological activity of the chitooligosacharides produced by the hydrolytic activity of the recombinant enzyme. Analysis of the sequence and molecular anchorage revealed by the chitosanase of C. violaceum ATCC 12472, named CvCsn46, has 360 amino acids, including a signal peptide, a carbohydrate binding domain, a catalytic domain that belongs to the GH46 family, and has Glu138, Asp156 and Thr161 as catalytic amino acids. The recombinant protein was produced and purified by affinity chromatography, showing two bands in the polyacrylamide gel with apparent masses of 38 kDa and 36 kDa, both were identified as chitosanase of C. violaceum ATCC 12472 by mass spectrometry. CvCsn46 showed optimal conditions for its enzymatic activity at pH 6 and 50 ° C and was stable in the pH range 2 to 12, maintaining at least 80% of its activity. The enzymatic activity of chitosanase was strongly inhibited by SDS, β-mercaptoethanol and by the metal ions Fe2+ and Hg2+ and stimulated by DTT, by the ions Ca2+, Co2+, Cu2+ and mainly Mn2+ which increased CvCsn46’s activity up to 3.5x. The enzyme kinetics of this chitosanase showed a sigmoidal curve with a Vmax of 10818 μmol/min.mg and Hill's coefficient of 3.9. CvCsn46 was able to degrade chitosan in products with a degree of polymerization from 1 to 7 and these products showed antifungal activity against a species of Lasiodiplodia sp. Scanning electron microscopy analyzes showed that the chitooligosacharides produced by CvCsn46 induced inhibition of fungus growth, promoting morphological changes such as reduction of the hypha size and aggregation. The present work demonstrated that CvCsn46 is an active enzyme and can be an effective tool to produce glucosamine and chitooligosaccharides with biological activity.